Le rôle des juridictions supranationales de la CEMAC et de l'OHADA dans l'intégration des droits communautaires par les Etats membres - Fipa Nguepjo, Jacques (Université Paris 2, 2011)
La Cour de Justice Communautaire (CJC), la Cour des Comptes Communautaire (CCC) et la Cour Commune de Justice et d’Arbitrage (CCJA) sont les trois juridictions supranationales créées respectivement par les traités de la CEMAC et de l’OHADA pour renforcer les nouveaux processus d’intégration économique et juridique des Etats membres. Dans la mesure où ces juridictions exercent un contrôle juridictionnel déterminant de la norme communautaire, le premier contrôle étant effectué par les juridictions nationales des Etats parties, la conception, l’organisation, le fonctionnement, les caractéristiques, les rôles ou compétences de ces juridictions nouvelles ainsi que la destinée des décisions qu’elles rendent dans leurs fonctions strictement judiciaires ou dans celles accessoires d’appui à la procédure arbitrale, présentent un intérêt digne d’une recherche doctorale. S’il est apparu que des jalons supplémentaires d’efficacité des nouveaux processus d’intégration ont été plantés par la création desdites juridictions, il a également été constaté que des pesanteurs d’ordre juridictionnel, structurel ou fonctionnel continuent d’en retarder la vitesse de croisière. Les solutions que nous avons proposées pour surmonter ces difficultés se regroupent en une réorganisation des juridictions communautaires, une répartition claire des compétences entre elles, un renforcement de la procédure de contrôle du droit communautaire, une vulgarisation permanente du droit de l’intégration, une revalorisation des titres exécutoires, une clarification des fonctions du juge d’exécution, une restriction du domaine de l’immunité d’exécution, un réaménagement des procédures de recouvrement, une formation continue des acteurs de la justice, une amélioration de leur condition de travail et de vie, une résurgence de l’éthique morale, une réelle indépendance de la justice… C’est dire que l’étude met un accent sur les obstacles qui entravent les nouveaux processus d’intégration et propose des solutions pour parfaire les textes législatifs et leurs interprétations jurisprudentielles, dans la perspective d’accélérer le développement économique des Etats concernés en particulier, pour une meilleure prospérité globale des économies mondiales. = The Communautary Court of Justice (CCJ), the Communautary Court of Account (CCA) and the Common Court of Justice and Arbitration (CCJA) are the three supranational jurisdictions respectively created by EMCAC and OHBLA treaties to reinforce the new processes of economical and judicial integration for their member States. In the measure where these jurisdictions are competent to exercise a juridictional control, by determining the communautary norms, the first control being carried out by the national juridictions, the conception, the organisation, the functioning, the characteristics, the roles or competences of these new jurisdictions and also the destiny of the decisions they rend in their strictly judiciary functions or in their accessory functions of supporting the arbitral procedure, present an interest worthy of a doctorate research. If it appears that the supplementary Milestones of efficiency of the new processes of integration had been installed by the creation of the said jurisdictions, it had also been observed that the gravities of jurisdictional, structural or functional order continue to delay the speed of cruise. The solutions that we have proposed to overcome these difficulties involves the reorganization of communautary jurisdictions, the clearly distribution of competences between them, the reinforcement of the communautarian law control procedure, a permanent vulgarisation of integration law, a revalorisation of executary titles, a clarification of immunity of execution domain, a development of the recovery procedures, a continual training of judicial actors, and improvement of their working and living conditions, a resurgence of moral ethic, a real independence of the Justice… This means that the study put a stress on the obstacles which hold up the new processes of integration and propose solutions to perfect the legislative texts and their jurisprudential interpretations, in the perspective of accelerating the economic development of the concerned States, for the best global prosperity of the world’s economies.
https://assasrecherche.u-paris2.fr/ori-oai-search/notice/view/2011PA020030
Keywords: Advisory opinion; Africa; Afrique; Afrique centrale; Arbitrage; Arbitragem; Arbitral sentence; Arbitration; Avis consultatif; CCJA; CEMAC; Central Africa economic and monetary community; Communautary court of justice; Communautary judge; Competent authority; Compétence (droit) - Afrique; Compétences; Conflicts; Conflit; Corruption; Cour Commune de Justice et d'Arbitrage; Cour de justice communautaire (CJC); Cour des comptes communautaire; Court of account; Droit commercial (droit international); EMCAC; Economic integration; Efficacité; Enforceable provisional execution; Enforcement; Executory title; Exequatur; Exécution provisoire; Harmonisation; Immunity of execution; Immunité d'exécution; Imperceptibility; Insaisissabilité; Integration; International unification; Intégration; Intégration économique; Juge communautaire; Juge national; Juridiction - Afrique; Jurisdiction; National court; OHADA; OHBLA; Organisation for the harmonisation of business law in Africa; Preliminary ruling; Provisional execution; Reforms; Regulation; Renvoi préjudiciel; Réformes; Régulation; Rôle; Sentence arbitrale; Supranationality; Supranationalité; Titre exécutoire; Traité; Treaty; UEAC; UMAC; Unification internationale

L'Application effective du droit communautaire en Afrique centrale - Tchuinte, Joël (CY Cergy Paris Université, 2011)
La réussite du processus d'intégration régionale dépend essentiellement de sa réception et de sa sanction dans les ordres juridiques internes. la crainte principale réside dans l'ineffectivité des règles communes dans les Etats parties. Ceux-ci peuvent en effet refuser de tirer toutes les conséquences du transfert des compétences qu'ils effectuent librement au profit des organes communautaires.Si la CEMAC peine aujourd'hui à trouver le juste équilibre entre les objectifs ambitieux qu'elle affiche et la capacité des Etats membres à les réaliser en commun, l'OHADA arrive, dans un environnement difficile, à tracer une voie qui est porteuse d'espoirs.
Keywords: African community law; Afrique centrale; CCJA; Communauté Economique et Monétaire de l'Afrique Centrale; Constitutionnal law; Cour Commune de Justice et d'Arbitrage; Cour de justice CEMAC; Droit communautaire africain; Droit constitutionnel; Droit international; Droit interne; Droit public; Droits constitutionnels africains; EMCCA; EMCCA Court; Effectivité; France; Intégration régionale; OHADA et CEMAC; OHBLA; OHBLA Court; Organisation pour l'harmonisation en Afrique du droit des affaires; Public law; Regional integration

De la réforme et de l'harmonisation du droit des sûretés dans un contexte de mondialisation de l'économie : vers un retour au paradigme de l'uniformisation du droit? - Leduc, Antoine (Université de Montréal, 2011)
La réforme et l’harmonisation du droit des sûretés mobilières sont à l’ordre du jour de plusieurs organisations internationales, car il est admis qu’un régime de sûretés efficient favorise l’accès au crédit à de faibles coûts. L’harmonisation de ce droit comporte deux volets. D’une part, dans l’Occident industrialisé, les efforts d’harmonisation vont de la réforme des droits internes à l’établissement de régimes spéciaux relativement à des biens spécifiques (principalement les biens mobiles de grande valeur, tels les aéronefs, le matériel ferroviaire roulant et les satellites, et les biens incorporels, comprenant les créances, valeurs mobilières, actifs financiers et titres intermédiés). Ces efforts d’harmonisation démontrent que d’un point de vue systémique, malgré quelques différences notables, les régimes nord-américains et européens sont fondés sur des principes similaires et atteignent des résultats comparables. En résulte l’émergence d’un ordre juridique transnational en droit des sûretés mobilières, fondé sur les principes de la primauté de l’individu et la reconnaissance du droit de propriété de l’individu dans ses biens, mis en œuvre grâce à l’État de droit. D’autre part, les institutions financières internationales encouragent l’établissement de régimes de sûretés dans les pays en voie de développement qui obéissent aux mêmes critères que ceux de l’Occident, en insistant sur les réformes institutionnelles et juridiques visant l’établissement d’une bonne gouvernance et l’État de droit. Cependant, une transposition des régimes occidentaux ne peut se faire sans heurts dans les pays en voie de développement, notamment pour des raisons socio-culturelles et politiques. Lorsque les principes de la primauté de l’individu, de la propriété individuelle et de l’État de droit ne sont pas reconnus dans un pays donné, la réforme et l’harmonisation du droit des sûretés s’en trouvent compromis. La démonstration de l’état d’avancement de la réforme et de l’harmonisation du droit des sûretés dans les pays occidentaux industrialisés est faite grâce à une comparaison du Uniform Commercial Code, du Code civil du Québec, des Personal Property Security Acts des provinces canadiennes de common law, des principes des droits français et anglais, de l’influence du droit communautaire sur les pays membres de l’Union Européenne. Sont analysés, aussi, dans cette optique, les principaux instruments de l’harmonisation du droit émanant des organisations internationales. Par ailleurs, deux études de cas relatifs à la réforme du crédit foncier en Égypte et à la réforme de l’urbanisme et de l’habitat en République démocratique du Congo, viennent étayer les difficultés que rencontrent les institutions internationales, telles la Banque mondiale et l’ACDI, dans le cadre de projets de réformes visant la bonne gouvernance et l’instauration d’un véritable État de droit, en partie à cause d’un pluralisme des ordres juridiques de ces pays. The reform and harmonization of secured transactions on movable (or personal) property is fostered by international organizations, on the assumption that an efficient regime of secured transactions will give access to affordable credit to a large number of persons and corporations. Such reform and harmonization process can be explained according to its two main features. Firstly, in Western and developped countries, the focus is on endeavours to harmonize the various regimes internally and to establish special regimes with respect to specific assets (for instance, high value mobile equipment, such as aircrafts, rolling stock or satellites, on the one hand, or incorporeal property, including securities, financial assets or security entitlements, on the other hand). Even though some differences remains from a systemic point of view, north american and european regimes are based on similar principles and achieve comparable results. It is therefore possible to see the emergence of a transnational legal order in the law of secured transactions, based on individuals and the enforcement of their rights of ownership, ascertained by the Rule of Law principle. Secondly, international financial institutions are encouraging the implementation of secured transactions regimes in developing countries along the same criteria as those used in Western developed countries, in the context of institutional and legal reforms under governance and rule of law projects. However, Western regimes must be adapted and customized before they are transplanted into a developing country. Indeed, for socio-cultural and political reasons, it is not possible to establish the same kind of regime therein. When individual rights and freedoms, including the right of ownership and the Rule of Law, are not recognized, the reform and harmonization of secured transactions is not likely to happen. The status of advancement of the reform and harmonization of secured transactions in the developed world is illustrated by a comparison between the Uniform Commercial Code, the Civil Code of Québec, the Personal Property Security Acts of canadian common law provinces, the applicable principles under both French and English Law, and the influence of European Law on its member states. An analysis of the main harmonization instruments proposed by international organizations is also conducted. Finally, the pitfalls of governance and rule of law reform projects are well described by two case studies. The first one deals with real estate and mortgage law reforms in Egypt, with a goal to encourage affordable access to housing; the second one is about urban planing and housing reforms in the Democratic Republic of Congo. The existence of a multiplicity of legal orders in these countries explains the difficulties encountered in such reform processes.
Keywords: ACDI; African Customary Law; Banque mondiale; Civil Law; Common law; Comparative law; Droit civil; Droit comparé; Droit coutumier africain; Droit et développement; Droit islamique; Harmonisation; Islamic Law; Law and Development; Rule of Law; Secured transactions; Sûretés mobilières; World Bank; État de droit

Can OHADA Increase Legal Certainty in Africa? - Beauchard, Renaud; Kodo, Mahutodji Jimmy Vital (The World Bank, 2011)
This paper describes the origins, structure, and practical impact of the Organization for the Harmonization of Business Law in Africa (OHADA). It analyzes the institutional framework created via the OHADA Treaty and the legal, jurisprudential, and functional challenges that OHADA Member States are still grappling with. Details of the nine substantive laws that have so far been ratified as uniform acts by means of the treaty have also been provided. The authors conclude that in making OHADA law effective, Member States face continuing and substantial resource deficits, institutional deficiencies, language ambiguities, and intransigent official attitudes toward the need for appropriate mechanisms for the pursuance and enforcement of OHADA laws and processes.

Multi-Membership and the Effectiveness of Regional Trade Agreements in Western and Southern Africa: A Comparative Study of ECOWAS and SADC - Afesorgbor, Sylvanus Kwaku; Van Bergeijk, Peter A. G. (Proceedings of the German Development Economics Conference, 2011)
Using a gravity model for 35 countries and the years 1995-2006 we estimate the impact of regional trade agreements in Africa (in particular ECOWAS and SADC) and compare this to the a benchmark of North South trade integration (Europe‟s preferential trade agreement). We find that  ECOWAS and SADC membership significantly increases bilateral trade flows (and by more than for example preferential trade agreements with the EU do),  SADC membership has a stronger impact compared to ECOWAS and  that the impact of multi-membership critically depends on the characteristics of the overlapping RTA We find a positive impact if an additional membership complements the integration process of the original RTA: overlapping memberships had a significant positive effect on bilateral trade within the ECOWAS bloc but it is insignificant for SADC.

Comparative regionalism: a new research agenda - Börzel, Tanja A. (KFG The Transformative Power of Europe, 2011)
After the end of the Cold War, students of International Relations observed an expansion of inter-state activities at the regional level. Regional and sub-regional groupings appeared to gain momentum as the way in which countries cooperate and should cooperate to pursue peace, stability, wealth and social justice. The surge and resurgence of regionalism has triggered the proliferation of concepts and approaches. The focus of this paper will be on processes and structures of state-led regionalism driven by the delegation of policies and political authority to regional institutions. Based on this understanding of regionalism, the existing literature will be reviewed with regard to three general questions. These questions do not only require research across regions but also allow developing a common research agenda to accumulate knowledge generated about specific regions. First, what are the outcomes of regionalism? How can we describe and compare the results of the delegation of policies and political authority? Second, what are the drivers of regionalism? Why do some governments choose to delegate policies and political authority while others do not? Finally, what are the internal effects of regionalism? How does the delegation of policies and political authority impact back on the domestic structures of the states involved?
Accepted: 2018-06-08T07:36:10Z

Economia política da integração regional na África ocidental : a União Econômica e Monetária (UEMOA) como estratégia para o desenvolvimento regional - Fernandes, Lito Nunes (Universidade Federal do Rio Grande do Sul, 2011)
No início do novo milênio, a formação de blocos econômicos regionais foi-se apresentando como estratégia de promoção do desenvolvimento para os países periféricos. Tratando-se da África Ocidental, a integração de seus pequenos países com vista a usufruir as vantagens decorrentes desse processo resulta em última instância, a solução potencial de seus diversos problemas, e a resposta da sua marginal posição na atual globalização. São países que enfrentam malformações estruturais e situações dramáticas de pobreza e miséria produto de séculos de exploração, repartição desinteressada e agressiva de seus territórios a beneplácito da acirrada competência imperialista e da colonização posterior. Neste sentido, esta tese propõe responder duas perguntas: quais as causas do estabelecimento de uma união econômica e monetária numa região sem condições prévias e se esta integração está conduzindo ou não a seus países ao desenvolvimento. A mesma parte da hipótese de a integração regional na atualidade ser a alternativa mais viável para garantir a sustentabilidade do processo de desenvolvimento nesta região. O objetivo da tese é analisar a dinâmica regional da integração da UEMOA, que surgiu contrária à visão convencional das teorias monetárias, como estratégia do desenvolvimento, e em seguida, vincular seus resultados ao desenvolvimento econômico dos países da região. Ressalta-se que foi dada prioridade a literatura africana, não por rechaço ou demérito da produção ocidental sobre o tema, mas pelo entendimento de que, neste aspecto específico, as opiniões dos autores africanos dariam um melhor enriquecimento e uma visão mais realista sobre o tema. Conclui-se que independentemente de não seguir as diretrizes convencionais, a integração da UEMOA está sendo fundamental para o desenvolvimento de seus países, segundo a realidade da região. Portanto, sua análise deve ser realizada acorde a especificidade local, sem esquecer as conseqüências do seu passado histórico que ainda repercutem negativamente na sua situação socioeconômico. Ou seja, sua valoração não deve seguir o modelo das regiões desenvolvidas ou emergentes, mas sim desde a perspectiva das duras realidades da região.
URI: https://lume.ufrgs.br/handle/10183/36098
Keywords: Afrique Occidentale; Blocos econômicos; Desenvolvimento regional; Development; Integração econômica; Integração regional; Intégration régionale; Países em desenvolvimento; Regional integration; UEMOA; WAEMU; Western Africa; África Ocidental

Integração Econômica Regional Na África Ocidental: Uma Visão Crítica - Fernandes, Lito Nunes; Boukounga, Jean Christian; Júnior, José Fernandes (Conjuntura Austral, 2011)
Os blocos econômicos regionais estão sendo na atualidade instrumentos importantes na luta contra a pobreza, subdesenvolvimento e inserção na economia global e a África Ocidental (AO) apresenta como uma das regiões mais interessadas. Consciente desta realidade, o artigo trabalha com a hipótese de a integração ser a condição sine qua non mesmo que insuficiente para o desenvolvimento da região. O objetivo é demonstrar as diversas iniciativas integracionistas na AO, os logros obtidos apesar da especificidade da região, assim como as adversidades e obstáculos encontrados. Conclui-se que apesar dos problemas e mesmo que essa integração não siga os padrões ocidentais, o estabelecimento de uma união monetária numa zona sem condições mínimas por si só, é um êxito, opondo desta forma as críticas da literatura ocidental que quase sempre catalogam de fracassadas as integrações africanas.
Keywords: Integração regional; Regional integration; Western Africa; Western Countries; desenvolvimento; development; ocidente; África Ocidental

Challenges to regional intergration in the SADC region : a legal perspective - Mwanawina, Ilyayambwa (North-West University, 2011)
The Southern African Development Community (SADC), formerly known as the Southern African Development Coordination Conference (SADCC), is an organization of Southern African states initially formed to reduce economic dependence on South Africa (then an Apartheid state) and to harmonize and coordinate development in the region. The vision and mission of SADC reach well beyond the harmonization of development within the region. It extends to fields that include political stability, peace building, the maintenance of security and justice as well as economic cooperation. The attainment of these goals requires well co-ordinated regional mechanisms; as such over the past decade member states have paid particular attention to the possibility of attaining these goals through regional integration. The transformation from SADCC to SADC indicated that the body would no longer be a loose association (conference) of states but rather a regional body that would have a legally binding effect on its member states. The question is, when the member states assembled in Windhoek, August 1992, did they create an institutional framework, and policies that would have enough legal force to ensure that the institutional agenda of integration is not defeated by member states? The argument of this dissertation is that the Treaty and the policies established afterwards contain principle imperfections that are self defeating for the pursuance of regional integration. The work will begin by discussing regional integration in general, highlighting the historical origins of SADC as well as the role of the African Union. The work will then discuss the dimensions and functioning of SADC, laying the foundation for a proper critique on how the institutional framework contains inherent weaknesses that eventually hinder the progression of SADC. The dissertation ultimately will discuss and benchmark the European Union against SADC, in an attempt to extract important lessons for the progression of SADC.
Accepted: 2016-01-10T22:52:56Z https://repository.nwu.ac.za/handle/10394/15788
Keywords: Africa; Interregionalism; Southern